UJI EFEKTIVITAS SABUN TRANSPARANANTI JERAWAT MINYAK ATSIRI KULIT BUAH JERUK PONTIANAK (Citrus nobilis Lour. var. microcarpa) TERHADAP ISOLAT (Propionibacterium acnes) - ., Mariani Prapanta (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2014)
Acne vulgaris is one of dermatosis problem’s that appear most at teenagerand caused by Propionibacterium acnes bacteria that had important role at acnes’phatogenesis. The purpose of this research was to know the effectiveness ofantibacterial activity from essential oil of pontianak orange peel that is formulatedas a transparent soap. The transparent soaps were formulated using the isolate ofPropionibacterium acnes and disc diffusion method (Kirby-Bauer test). Theisolate of Propionibacterium acnes was a result from sample isolation of subjectsthat had a dermatosis problem such as acnes. The essential oils were formulated asa transparent soap with variation concentration of active content into threeformulas, FI (0,025%); FII (0,05%); and FIII (0,1%) The result of transparentsoap then got physical and chemistry analysis such as color, fragrance, texture,foaming power, transparency, water content, free alkali, fatty acids total,unsaponifiable fraction, the height of foam, pH, and antibacterial activity of thetransparent soap. The results the analyzed using R-Commander Program 1.24.1.The results of evaluation showed that the transparent soaps from the essential oilof Pontianak orange peel were acceptable but there were few evaluation that werenot acceptable compared to the SNI standard. The effectiveness of antibacterialactivity from the transparent soap showed that F3 with 0,1% concentration ofessential oil give the best effectiveness with 20,84 ± 1,56 mm zone of inhibition. Keywords: Essential oil, Pontianak orange peel, Propionibacterium acnes, isolate, transparent soap